2016
DOI: 10.1080/13811118.2016.1175394
|View full text |Cite
|
Sign up to set email alerts
|

Mental Pain and Suicidal Tendencies in Sexual and Physical Abuse Victims

Abstract: We examine differential effects of mental pain and suicidal tendencies in female victims who have been sexually and physically abused, hypothesizing that sexual abuse victims report more mental pain and suicidal tendencies than physical abuse victims. A group of 98 women completed questionnaires that measured mental pain, suicidal tendencies and thoughts, and demographic details. Sexual abuse victims suffered more mental pain than physical abuse victims while the physical abuse victims demonstrated more repuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Our tentative results found that depressive symptoms, suicide intentions, and suicide plans were associated with sexual abuse. In adjusted models, people who reported sexual and physical abuse had an increased risk of suicide plans, which is consistent with an Israeli study [41]. There was also a correlation between sexual abuse and depressive symptoms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our tentative results found that depressive symptoms, suicide intentions, and suicide plans were associated with sexual abuse. In adjusted models, people who reported sexual and physical abuse had an increased risk of suicide plans, which is consistent with an Israeli study [41]. There was also a correlation between sexual abuse and depressive symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…Compared to students with no physical abuse, individuals who suffered physical abuse had 2.73, 2.72, 3.19 times increased odds of reporting depressive symptoms, suicide intentions and suicide plans. Inbar Kremer also said, such as physical abuse victims more attractive to death [41]. One study estimated that a quarter of children had experienced physical abuse worldwide [45].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of psychiatric and behavioral effects, childhood sexual but not physical abuse was associated with suicidal behaviour [47], self-injury [51], adulthood sexual dysfunction [53], and having at least two symptoms of schizophrenia [48]. Youth with childhood sexual abuse also reported more externalizing and internalizing problems over time than maltreated but non-sexually abused youth [46], and victims of childhood sexual abuse reported more severe mental pain compared with physical abuse victims [54]. Scholars have also argued that childhood sexual abuse is associated with experiences or feelings unique to sexual victimization relative to other abuse and neglect experiences; for example, traumatic sexualization, betrayal, stigmatization, attributions of responsibility as well as feelings of guilt and shame collectively may impact victims of childhood sexual abuse more profoundly and/or differently than victims of other abuse experiences [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing recognition that mental pain is one of the crucial psychological risk factors for understanding suicidal ideations and behaviors (e.g., Ducasse et al., ; Kremer, Orbach, & Rosenbloom, ; Orbach, Mikulincer, Gilboa‐Schechtman, & Sirota, ; Orbach, Mikulincer, Sirota, & Gilboa‐Schechtman, ). Shneidman (, ) was the first to systematically define mental pain and to delineate the mental pain – suicidality hypothesis.…”
mentioning
confidence: 99%